(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic kidney disease (CKD) significantly affects oral health, leading to bone resorption, periodontal disease, and xerostomia, which impact prosthetic treatment outcomes. This literature review examines the comparative effectiveness of removable and fixed prosthetic solutions in CKD patients. Factors such as bone density, periodontal health, and systemic conditions are analyzed to determine optimal prosthetic choices. The study highlights recent innovations, including PRF technology and biocompatible materials, to improve prosthetic success rates. Multidisciplinary collaboration between dentists and nephrologists is emphasized for individualized patient care.